ASSESSMENT OF MICROCIRCULATION IN PATIENTS WITH GENERALIZED PERIODONTITIS DURING TREATMENT WITH AUTOPLASMA AND HYALURONIC ACID - Vyshnevska, H.O.; Shnaider, S.A.; Reyzvikh, O.E.; Babenia, H.O.; Христова, М.Т. (World of Medicine and Biology, 2022)
The relevance of the study of microcirculation is determined by the fact that the nature of its violations can establish the stage of pathological changes in organs and tissues, as well as choose treatment tactics. The aim was to study the dynamics of hemodynamic changes in patients with generalized periodontitis, after treatment with a combined method of plasmagel, i-PRF and hyaluronic acid according to Doppler ultrasound. Diagnosis of microhemodynamic changes in periodontal tissues was performed by ultrasound Doppler. After the treatment it is clear that the improvement of blood flow occurred in both groups, in the main group (after 1 year –1.217±0.035 cm/sec, after 2 years – 1.297±0.061 cm/sec), in the comparison group (after 1 year – 0.729±0.031 cm/sec, after 2 years – 0.632±0.025 cm/sec). In the long run, after 2 years, it can be noted that the indicator in the comparison group gradually begins to decline, and in the main group remains at a high level. Thus, the main group showed a significant increase in linear maximal systolic blood flow velocity (1.297±0.061 cm/sec) and an increase in volumetric maximal systolic blood flow velocity (0.037±0.001 ml/sec).
Keywords: periodontal vessels; dopplerography; plasmagel; i-PRF; regenerative techniques